Taking the fight to them: neighborhood human rights organizations and domestic protest - Bell, Sam R.; Bhasin, Tavishi; Clay, K. Chad; Murdie, Amanda (My University, 2015)
This article examines how human rights international non-governmental organizations (hereafter HROs) can increase the level of political protest in neighboring states. Previous research suggests local activities of HROs help to generate mobilization for protests against governments. This article shows that the presence of HROs in neighboring states can be a substitute for domestic HROs; if domestic HROs are already flourishing, there will be less of a ‘neighbor’ effect. At sufficiently high levels of domestic HRO prevalence within a state, neighboring HROs help domestic HROs use institutionalized substitutes for protest mobilization strategies. Spatial econometric methods are used to test the implications of this theory. These results illuminate the role that non-governmental organizations play in these domestic political processes, and demonstrate the transnational nature of their activities.
Keywords: Human rights international non-governmental organizations; Political protest